Relationship between Government Financial Grants, Internal Revenue and Maternal Mortality Rate in South Africa - Muila, Seshoka L.; Ngwakwe, Collins C. (International Review of Management and Marketing, 2022)
Funding of public hospitals and access to quality health care is a universal problem especially in developing countries. This paper aims to examine the relationship between government financial grants, internal revenue and maternal mortality rate. Previous literature has suggested that to achieve better health outcomes, multiple factors including but not limited to finance must be taken into consideration. Secondary data from audited annual health reports (2014/15 – 2018/19) of the nine South African Provinces was analyzed with the employment of the panel data regression technique. Internal Government Revenue was statistically significant at a 5% level of significance (p < 0.05) and Government Financial Grant was not statistically significant (p >0.05). Maternal mortality rate is therefore dependent on internal revenue and not on government financial grants. The findings change the ancient saying that maternal health outcomes shall improve when the government pumps more finances into the health system. Instead, the study reveals that internal revenue generation has an impact on the maternal mortality rate thus bringing in another approach in the fight against maternal mortality. The study adds value to the public health administration in that it brings a different perspective on the fight against maternal mortality in South Africa.